Analisis Improvisasi Tenor Saxophone Chris Potter pada Karya “Wistful” - Purba, Bernard Zulfredo; Sanjaya, Singgih; Prasetyo, Agoeng (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This article discusses the analysis of Chris Potter's improvisation on the song Wistful. The author chose Chris Potter because he is an inspiration in playing jazz, because of his very high skills (virtuoso). The song Wistful was released on an album entitled "Unspoken", in 1997. The author is interested in the song Wistful because Chris Potter shows a calm side of himself, the processing of sound color in an ensemble, and the resulting saxophone sound is thick and very unique. Research methods: This study uses a qualitative method. The process is through library research, then audio research, then the author transcribes directly using a saxophone and writes it into staff notation. Results and discussion: The song Wistful has a three-part song form, namely A-A-B. Chris Potter tends to use a chordal approach, and several theories of approach such as 7-3 resolution, 3-b9, mode, passing note, linear chromaticism, neighbor tone, and cesh. Implication: the discussion in the article provides an analysis model for jazz improvisation on the tenor saxophone in general and Chris Potter's works in particular.